2017
DOI: 10.5005/jp-journals-10006-1483
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-based Cytology vs Conventional Cytology as a Screening Tool for Cervical Cancer in Postmenopausal Women

Abstract: Aim: To evaluate and compare the efficacy of liquid-based cytology (LBC) with conventional cytology (CS) as a screening tool for cervical cancer in postmenopausal women. Materials and methods:This was an observational crosssectional study conducted over one year. Subjects were recruited from patients attending the outpatient department of the Department of Obstetrics and Gynecology, King George's Medical University, Lucknow, Uttar Pradesh, India. Pap smear and LBC were taken in all subjects. In cases with susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Studies conducted by Budak M et al 12 and Qureshi S et al 31 reported more cases of SCC in LBC than in CPS. Studies done by Budak M et al 12 and Stabile S et al 28 reported more cases of AGS-NOS in LBC as compared to CPS.…”
Section: Discussionmentioning
confidence: 96%
“…Studies conducted by Budak M et al 12 and Qureshi S et al 31 reported more cases of SCC in LBC than in CPS. Studies done by Budak M et al 12 and Stabile S et al 28 reported more cases of AGS-NOS in LBC as compared to CPS.…”
Section: Discussionmentioning
confidence: 96%
“…[5] Also cytological pattern of the advanced atrophic menopause are influenced by dryness of the The mortality rate of cervical cancer can be significantly reduced if a woman is screened once when she is between the ages of 40-45 years. [6] In the last 15 years, new cytological techniques have been developed to improve the sensitivity of Pap smear. [7] LBC leads to significantly fewer unsatisfactory smears (with associated financial costs and anxiety for women).…”
Section: Introductionmentioning
confidence: 99%